AB0599 Relation between the deficit/deficiency of vitamin d and the depression/anxiety in patients with lupus in the department of rheumatology of the hospital of clinics. (12th June 2018) - Vazquez, M.A.; Ortiz, N.; Martínez, V.; Roman, L.; Bauman, K.; Melo, M.; Acosta, E.; Duarte, M.; Acosta Colman, I.
Abstract : Background: It has been postulated that low concentrations of 25-hidroxivitamin D serum [25 (OH) D] is associated with a greater prevalence of depression. People with deficient levels of vitamin D are more likely to experience mood disorders such as depression and anxiety. The vitamin D plays a role in the release of neurotransmitters such as serotonin and dopamine which is why is interesting the study of this in patients with systemic lupus erythematosus, who are discouraged from sun exposure. Objectives: Determine the association between the deficit/insufficiency of vitamin D and the anxiety/depression in patients with SLE of the Department of Rheumatology of the Hospital de Clínicas Methods: Observational study of longitudinal court based in a questionnaire according to the scale HADS ( Hospital anxiety and Depression Scale ) and the dosages of vitamin D performed on patients who entered the LUPUS PY cohort with prior informed consent. The dosage of vitamin D realised by chemiluminescence. Data and samples were taken in week 0 and week 24 and the prevalence of depression and anxiety and its association with vitamin D deficiency and insufficiency were identified. Patients with vitamin D deficiency or insufficiency were supplemented with vitamin D. For the descriptive analysis of the quantitative variables, average and SD were used, for the qualitative frequencies and percentages. For the analysis of association the test × 2 was used. The value of the p considered statistically significant was less than 0, 05. Results: In relation to the characteristics of the studied cohort, we can see that 90.5% were female, with an average age of 33±10.2 years. At week 0 the average value of vitamin D concentration was 31.8±10.2 ng/ml. It is found that 4, 48% of patients had depression and 33, 69% of patients have anxiety. In the week 24 the value of the average of vitamin D was of 31, 1±13, 6 ng/ml. It was observed in this week that 6% of patients presented depression and 12% of patients anxiety. In the analysis of association there was no association between vitamin D deficits and the presence of depression or anxiety of these patients both at the week 0 as a week 24 post vitamin D supplementation such, and as seen in table 1. Conclusions: A significant percentage of patients with deficient or insufficient vitamin D were found, as well as a considerable percentage had depression or anxiety, although no association was found between the state of this vitamin and the alterations of the studied mood. More studies are required that include more patients in order to obtain more conclusive results. Reference: [1] Okereke, Olivia I., Ankura Singh. "The Role of Vitamin D in the Prevention of Late-Life Depression."Journal of affective disorders198 (2016): 1–14. PMC . Web. 30 Jan. 2018. Disclosure of Interest: None declared